2006
DOI: 10.1299/jbse.1.136
|View full text |Cite
|
Sign up to set email alerts
|

Initial bFGF Distribution Affects the Depth of Three-dimensional Microvessel Networks in Vitro

Abstract: Control of three-dimensional (3D) microvessel formation is critical for regenerative medicine and tissue engineering because vessels are essential for the formation and maintenance of organ function. In order to function, tissues need an internal network of vessels. To introduce a 3D vessel network deep into the tissue, it is necessary to introduce 3D microvessel control which makes it a critical factor in regenerative medicine and tissue engineering. This study focuses on the effect of the concentration gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…For example, this model demonstrated that fibronectin incorporated in the matrix promoted elongation of the newly formed microvessels when aortic explants were embedded in a collagen matrix (Nicosia et al, 1993). Moreover, several studies using an in vitro angiogenesis model reported that ECs invaded into 3D matrices and underwent lumen formation in response to exogenous factors such as sphingosine-1phosphate (S1P), stromal cell-derived factor-1α, or basic fibroblast growth factor (bFGF) (Davis et al, 2000;Bayless and Davis, 2003;Saunders et al, 2006;Ueda et al, 2006) (Fig. 2A, upper panel).…”
Section: In Vitro Angiogenesis Modelsmentioning
confidence: 99%
“…For example, this model demonstrated that fibronectin incorporated in the matrix promoted elongation of the newly formed microvessels when aortic explants were embedded in a collagen matrix (Nicosia et al, 1993). Moreover, several studies using an in vitro angiogenesis model reported that ECs invaded into 3D matrices and underwent lumen formation in response to exogenous factors such as sphingosine-1phosphate (S1P), stromal cell-derived factor-1α, or basic fibroblast growth factor (bFGF) (Davis et al, 2000;Bayless and Davis, 2003;Saunders et al, 2006;Ueda et al, 2006) (Fig. 2A, upper panel).…”
Section: In Vitro Angiogenesis Modelsmentioning
confidence: 99%